Wave characteristics of reconfigurable elastic metamaterials based on a multi-stable structure. (1st April 2023) - Chen, Meng; Xiao, Boya; Feng, Yafei; Yang, Tao; Zhang, Han; Liu, Yu; Xu, Wenshuai; Jiang, Heng; Wang, Yuren
Highlights: Reconfigurable two-dimensional metamaterials were proposed by inducing curved beams to sustain multi-stable configurations. The configurations verifiably have different wave characteristics to tune elastic wave propagation at subwavelength scale. Based on this, an arbitrary position waveguide can be designed to control waves to travel in a particular direction. Abstract: Elastic metamaterials have been considered as important tools for vibration and noise reduction because of their subwavelength bandgaps. However, acritical problem hindering their practical application is the difficulty of constructing an adjustable unit cell that facilitates bandgap tuning. In this study, reconfigurable two-dimensional metamaterials based on four curved beams are developed such that they could sustain multi-stable configurations. Our calculations and experiments reveal that the developed unit cell can exhibit bidirectional phase transformations to three stable configurations. The three stable configurations have different wave characteristics, allowing for elastic wave propagation to be tuned at the subwavelength scale. Based on this tuneability, a waveguide can be designed and the wave direction of travel can be controlled. This study provides a novel approach for designing reconfigurable elastic wave materials, elastic wave logic circuits, and waveguides.